2001
DOI: 10.1038/35107134
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Broca's area in great apes

Abstract: Brodmann's area 44 delineates part of Broca's area within the inferior frontal gyrus of the human brain and is a critical region for speech production 1,2 , being larger in the left hemisphere than in the right 1-4 -an asymmetry that has been correlated with language dominance 2,3 . Here we show that there is a similar asymmetry in this area, also with left-hemisphere dominance, in three great ape species (Pan troglodytes, Pan paniscus and Gorilla gorilla). Our findings suggest that the neuroanatomical substra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
203
4
4

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 331 publications
(222 citation statements)
references
References 8 publications
11
203
4
4
Order By: Relevance
“…This possibility finds further support from a recent experiment based on the analysis of brain MRIs of three great ape species (Pan troglodytes, Pan paniscus and Gorilla gorilla) showing that the extension of BA 44 is larger in the left hemisphere than in the right. While a similar asymmetry in humans has been correlated with language dominance (Cantalupo & Hopkins, 2001), this hypothesis does not fit in the case of apes. It might be, however, indicative of an initial specialization of BA 44 for communication.…”
Section: Discussionmentioning
confidence: 81%
“…This possibility finds further support from a recent experiment based on the analysis of brain MRIs of three great ape species (Pan troglodytes, Pan paniscus and Gorilla gorilla) showing that the extension of BA 44 is larger in the left hemisphere than in the right. While a similar asymmetry in humans has been correlated with language dominance (Cantalupo & Hopkins, 2001), this hypothesis does not fit in the case of apes. It might be, however, indicative of an initial specialization of BA 44 for communication.…”
Section: Discussionmentioning
confidence: 81%
“…In humans, the leftward asymmetry in the planum temporale has been one of the most consistent asymmetries reported in the human brain (Beaton 1997;Shapleske et al 1999), whereas reports of population-level asymmetries in the frontal operculum have been far less consistent across studies (Keller et al 2007(Keller et al , 2009. Similarly, in chimpanzees, postmortem and in vivo analysis of the planum temporale have revealed significant leftward asymmetries (Hopkins & Nir in press) but this is less clear for the inferior frontal gyrus (Cantalupo & Hopkins 2001;Hopkins et al 2008;Keller et al 2009;Schenker et al 2010) and appears to depend on the landmarks used to define the region-of-interest as well as other factors.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, gross structural asymmetries have been observed in non-human primates, including chimpanzees, for homologues of areas implicated in human language and speech production (e.g. Gannon et al 1998;Cantalupo & Hopkins 2001;Hopkins 2007). …”
Section: Introductionmentioning
confidence: 99%
“…The planum temporale displays pronounced leftward asymmetry in most humans. Early studies reported that this feature was also present -although to a lower degree -in chimpanzees and other great apes (Cantalupo & Hopkins, 2001). Later, Taglialatela et al (2008) discovered that Broca's area homolog activates in chimpanzee brains when they communicate with gestures or vocalizations, which led to the theory that enlargement of Broca's area, and its role in communication, began before the evolutionary split between humans and chimpanzees.…”
Section: Perisylvian Region and Languagementioning
confidence: 98%